2019
DOI: 10.1177/1757975919875650
|View full text |Cite
|
Sign up to set email alerts
|

Appreciation for food, an important concept in mindful eating: association with home and school education, attitude, behavior, and health status in Japanese elementary school children

Abstract: Background: Appreciating food is an important concept in mindful eating, mentioned by advocates of an expanded model of mindful eating in 2016. With the exception of Japan, this concept is not common in many countries. Objective: We aimed to describe the role that appreciation for food has in the health of children from two perspectives: 1) association between children’s appreciation for food and their backgrounds, such as home and school educational experiences related to food, and 2) association between thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Awareness regarding the savoring of seasonal ingredients and celebration-specific meals and the appreciation for food in general is intrinsic to Japanese culture and they are closely related. In our previous study targeting children, appreciation for food was associated with attitudes toward healthy food, recommended food preferences, recommended food intake, breakfast consumption, indefinite complaint and BMI (Kawasaki and Akamatsu, 2019). Similar to the previous study, body image, which is the psychological factor directly relate to eating behavior, was correlated with the EMES.…”
Section: Discussionsupporting
confidence: 77%
“…Awareness regarding the savoring of seasonal ingredients and celebration-specific meals and the appreciation for food in general is intrinsic to Japanese culture and they are closely related. In our previous study targeting children, appreciation for food was associated with attitudes toward healthy food, recommended food preferences, recommended food intake, breakfast consumption, indefinite complaint and BMI (Kawasaki and Akamatsu, 2019). Similar to the previous study, body image, which is the psychological factor directly relate to eating behavior, was correlated with the EMES.…”
Section: Discussionsupporting
confidence: 77%
“…Mindfulness-based cognitive therapy (MBCT) is an adaptation that incorporates elements of CBT with mindfulness-based stress reduction, aiming to teach those at high risk of depressive relapse to stay well through learned skills [21,51]. Mindfulness with or without specific training in mindful eating may help people better control portion sizes and choose less calorie-dense foods while improving appreciation for food [52,53]. There is evidence that the improved appreciation (eating enjoyment-"joyful eating") of mindful eating strategies focusing on the sensory properties of food result in lower energy intake from unhealthy foods [54].…”
Section: Discussionmentioning
confidence: 99%
“… 18 Kawasaki and Akamatsu describe the role of appreciation for food in the health of children from two perspectives: 1) to describe the association between children’s appreciation for food and their backgrounds, such as home and educational experiences related to food, and 2) to describe the association between their appreciation for food and outcomes, such as attitude toward food, eating behaviors, and health status. 17 Their study found significant correlations between gender, educational experiences at home and at school, attitudes toward healthy food, recommended food preferences, breakfast consumption, and BMI (r=0.04, p < 0.05). Participants who had higher scores for appreciation for food, more home and educational experiences, better attitude towards healthy food items and recommended food preferences, and normal BMI consumed more frequently recommended foods.…”
Section: Mindful Eatingmentioning
confidence: 95%
“…16 This process also refers to the process of eating consciously healthy food when it is truly needed. 17 …”
Section: Mindful Eatingmentioning
confidence: 99%